Improving The Quality of Learning through Lesson Study Model Based on Innovation Class in SMPN 2, Menganti Gresik District - Supriyono Supriyono (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2021)
This study aims to determine the improvement of the quality of learning through the innovation-based class lesson study model school program. Research was conducted in three stages, namely: plan, do, see, for students in grades 7, 8, and 9. Techniques for collecting data through observation, and reporting. Data analysis was done in a qualitative, discrete manner. The results of the study showed the involvement of students, model teachers, teacher observers, Dispendik supervisors, committees and principals, parents / guardians of students and invitations from other schools were very active. Thus, improving the quality of learning through the innovation class based lesson study model school program has been very successful in improving the quality of expected learning.